Characterization of plastic debris and association of metals with microplastics in coastline sediment along the Persian Gulf. (August 2018) - Dobaradaran, Sina; Schmidt, Torsten C.; Nabipour, Iraj; Khajeahmadi, Nahid; Tajbakhsh, Saeed; Saeedi, Reza; Javad Mohammadi, Mohammad; Keshtkar, Mozhgan; Khorsand, Maryam; Faraji Ghasemi, Fatemeh
Highlights: We specify abundance, size and color distribution of plastic debris. We study metal contents of microplastics (MPs) in Persian Gulf area for first time. The majority of plastic items (79.3%) were smaller than 5 mm (defined size of MPs). There was significant difference between plastic number at different sampling times. Abstract: This study reports number, size and color distribution, and metal contents of microplastics as well as adherent sediments along the Persian Gulf. Samples were collected from 9 stations in summer 2015 with a sampling time interval of 10 days. Plastic size of 2–5 mm, and ≤0.25 mm with 45 and 33% and white and colorless plastics with 62 and 33% had the highest abundance considering number per m 2, respectively. In general, the majority of collected plastics (79%) were smaller than 5 mm (defined size for microplastics). The mean Al, Fe, Mn, Cd, Cr, Ni, Pb, Cu contents of plastic fragments were 115, 531, 32.2, 0.035, 0.915, 2.03, 4.59, and 3.6 μg g −1, respectively while the mean Al, Fe, Mn, Cd, Cr, Ni, Pb, Cu contents of sediments were 186, 3050, 127, 0.81, 5.01, 14.5, 48.6 and 5.43 μg g −1 respectively. There were significant differences between the abundance of plastic items as well as the all examined metal concentrations of microplastics and sediments at different sampling times. As there is no regular cleanup program in the studied areas, significant differences between plastic items number at different sampling times (with higher plastic items number at the first day of sampling) showed that a large number of plastic items may enter from beaches to the sea and become available to marine organisms.